DAMPAK KEPEMIMPINAN STRATEGIK PADA TRANSFORMASI DIGITAL MELALUI KOMPETENSI TEKNOLOGI KARYAWAN DAN KESIAPAN PERUBAHAN - Narwanto Nurcahyo; Dodi Setiawan Riatmaja; Dinda Sukmaningrum (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2026)
This research aims to analyze the impact of strategic leadership on digital transformation, considering the mediating roles of employee technological competence and change readiness. Digital transformation is increasingly becoming a strategic necessity for organizations, but its success is not solely determined by technological investment, but also by human resource readiness and leadership effectiveness in guiding the change process. The research employs a quantitative approach with an explanatory design through SEM-PLS. The sample consists of 210 employees from organizations in Yogyakarta who have been involved in digitalization initiatives, determined based on the rule of thumb of ten times the largest number of indicators. Analysis was conducted using SmartPLS 4.0 to assess construct validity, reliability, inter-variable relationships, and mediating roles. The results indicate that strategic leadership does not have a direct effect on digital transformation, but it significantly influences technological competence and change readiness. Both of these variables are proven to have a significant influence on digital transformation and act as mediators in the relationship between strategic leadership and digital transformation. These findings confirm that digital transformation is more effective when leaders are capable of strengthening digital competence and building change readiness in the work environment. This research contributes theoretically to understanding the internal mechanisms connecting strategic leadership with successful digital transformation, and provides practical implications for organizations in designing digital strategies based on technological and human readiness.